Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12951-020-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell nanoparticles suppress metastasis and modify the tumour-supportive activity of cancer-associated fibroblasts

Abstract: Background: Although accumulating evidence suggests that the crosstalk between malignant cells and cancerassociated fibroblasts (CAFs) actively contributes to tumour growth and metastatic dissemination, therapeutic strategies targeting tumour stroma are still not common in the clinical practice. Metal-based nanomaterials have been shown to exert excellent cytotoxic and anti-cancerous activities, however, their effects on the reactive stroma have never been investigated in details. Thus, using feasible in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 58 publications
(52 reference statements)
3
35
0
Order By: Relevance
“… 9 We have shown previously that magnetic iron particles (IOs) promote the osteogenic activity of progenitor cells. 23 In the current study, nHAp/IO composite was used as a delivery platform for the controlled release of functional microRNAs, ie, miR-21 and miR-124. We have tested the influence of the obtained composite nHAp/IO@miR-21/124 on viability, morphology, growth pattern, metabolic activity, mitochondrial potential and mitochondrial network development in murine pre-osteoblasts and pre-osteoblasts cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 We have shown previously that magnetic iron particles (IOs) promote the osteogenic activity of progenitor cells. 23 In the current study, nHAp/IO composite was used as a delivery platform for the controlled release of functional microRNAs, ie, miR-21 and miR-124. We have tested the influence of the obtained composite nHAp/IO@miR-21/124 on viability, morphology, growth pattern, metabolic activity, mitochondrial potential and mitochondrial network development in murine pre-osteoblasts and pre-osteoblasts cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that nHAp doped with IOs after exposition to the magnetic field promotes the expression of osteogenic markers in osteoblasts through integrin alpha-3 (INTa-3) activation, simultaneously inhibiting osteoclasts activity. 23 The nHAp/IOs composites reduced tartrate-resistant acid phosphatase activity (TRAP) and cathepsin K – two major regulators of osteoclasts metabolism. Moreover, we showed that nHAp doped with IOs could trigger apoptosis in osteoclasts via activation of BAX-p21-p53 and CASP-9 axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the combination therapy of nanomaterials and chemotherapy, nanoparticles affect the gene expression and secretion of CAFs, thereby altering their intrinsic interactions with malignant cells and affecting the protumor activity of the TIME. It has been demonstrated that Au-Ag nanoparticles achieve remarkable metastasis-suppressing activity by directly inhibiting adenocarcinoma cell proliferation, as well as indirectly by affecting cancer-associated fibroblasts by reducing their cancer-promoting function and regulating their secretory profiles [ 68 ]. In addition, due to the off-target distribution of anticancer nanoparticles to CAFs, researchers have exploited nanoparticles that can genetically modify CAFs into cells producing secretable TNF-related apoptosis-inducing ligand (sTRAIL) efficiently in situ, leading to apoptosis in the adjacent tumor cells in mice [ 69 ].…”
Section: Targeted Therapy Of Cells In the Tumor Immune Microenviromentioning
confidence: 99%
“…The peptide liposome FH-SSL-Nav exhibited increased cellular uptake and cytotoxicity in vitro , as well as improved antitumor efficacy in a Hep G2 tumor mouse model. A recent report 119 has shown that the tumor cell-promoting behavior of CAFs can be attenuated by gold-core silver-shell hybrid nanomaterials. In the in vivo study, the nanomaterial showed promising results in inhibiting tumor metastasis.…”
Section: Targeting the Tumor Biological Microenvironmentmentioning
confidence: 99%